READING HABITS AMONG STUDENTS OF UNIVERSITAS ATMA JAYA YOGYAKARTA - Sukci, L. Bening Parwita; Fitriati, Anna (Kantor Pelatihan Bahasa dan Budaya, Universitas Atma Jaya Yogyakarta. Gedung Santo Alfonsus, Jl. Mrican Baru No.28, Mrican, Caturtunggal, Kec. Depok, Kabupaten Sleman, Daerah Istimewa Yogyakarta 55281 Phone: (0274) 514319 Email: kpbb@uajy.ac.id, 2025)
Some research results show that Indonesian people have low reading habits, rank 70 in the world according to PISA and rank 3 in ASEAN. On the other hand, reading habits help students improve their academic performance. This research tried to find out the reading habits among Universitas Atma Jaya Yogyakarta students. A questionnaire using Google Form was employed to find the data. With the help of language lecturers, the questionnaire was distributed to 327 students from various study programs. From the data collected, it was found out that students only 38% have habits to read, 11% do not have reading habits and 51% do not know whether they have a reading habit or not since they only read when given a task. Furthermore, it was found that respondents only spend less than one hour daily reading.